A limit theorem for Markov decision processes - Mathias Staudigl (Bielefeld University, Institute of Mathematical Economics (IMW), 2013)
In this paper we prove a deterministic approximation theorem for a sequence of Markov decision processeswith finitely many actions and general state spaces as they appear frequently in economics, game theory and operations research. Using viscosity solution methods no a-priori differentiabililty assumptions are imposed on the value function. Applications for this result can be found in large deviation theory, and some simple economic problems.
urn:nbn:de:0070-pub-26740390
Keywords: C02; C44; C61; 330; Markov decision processes; optimal control; viscosity solutions; stochastic approximation